Bibliometric analysis of nanotechnology in spinal cord injury: current status and emerging frontiers - Gu, XiaoPeng; Zhang, SongOu; Ma, WeiHu (Frontiers in Pharmacology, 2024)
ObjectiveThe objective of this study was to analyze the impact of nanotechnology on the treatment and recovery of spinal cord injury (SCI), a condition that has profound global effects on physical and psychological health.MethodsWe utilized the Web of Science Core Collection to obtain bibliometric data. With the tools such as VOSviewer and CiteSpace, we conducted a comprehensive review of 422 relevant publications to identify research trends and influential works in the field of nanotechnology applied to SCI.ResultsThe analysis revealed significant contributions from both China, Sweden and the United States, and pinpointed inflammation, apoptosis, and nano-drug delivery as the primary areas of focus in current research, with emerging trends evident in recent literature.ConclusionNanotechnology hold great potential to revolutionize the treatment of SCI through targeted therapeutics and modulation of pathological processes. This study provided valuable insights into the evolving landscape of SCI research, underscoring the importance of continuous innovation and interdisciplinary collaboration.